PENERAPAN AKAD IJARAH PADA USAHA SERVIS ELEKTRONIK TUAN YONTRIONO - Imroatul Maulida; Muhammad Syarofi; Yuan Gang Tsai (Yayasan Haiah Nusratul Islam, 2025)
This study explores the application of the Ijarah contract in the electronic service business managed by Mr. Yontriono, a small and medium-sized enterprise (SME) in the electronics repair sector. The business offers various services, including repairing household appliances such as televisions, refrigerators, washing machines, and other electrical installations, with a focus on providing transparent pricing and convenience for customers. The study aims to analyze the practical implementation of the Ijarah contract, which is based on Islamic economic principles, in the service sector, where the exchange of services is evident. The study used a qualitative research method, specifically a case study approach, gathering data from interviews and observations with the business owner. The results showed that the Ijarah contract is effectively applied in the service transactions, with a clear agreement on the costs and timeline of repairs. The financial reports from the business indicate positive results, with healthy cash flow, low operational expenses, and a significant increase in capital due to profits. This demonstrates the viability and growth potential of the business, while adhering to Islamic economic principles.